Quality of life ten and more years after restorative proctocolectomy for patients with familial adenomatous polyposis coli - Ganschow, Petra; Pfeiffer, Ulrike; Hinz, Ulf; Leowardi-Bauer, Christine; Herfarth, Christian; Kadmon, Martina (Diseases of the colon & rectum, 2010)
PURPOSE: - Few studies on long-term quality of life after restorative proctocolectomy and ileal pouch-anal anastomosis have been published. Most of them survey a mixed patient population of familial adenomatous polyposis and ulcerative colitis. The present study analyzes long-term results more than 10 years after ileal pouch-anal anastomosis for patients with familial adenomatous polyposis, exclusively. - METHODS: - One hundred thirty-five patients who underwent ileal pouch-anal anastomosis more than 10 years ago were identified from the prospective familial adenomatous polyposis registry at Heidelberg University hospital. They received the German version of the health-specific Short Form 36 Health Survey and the disease-specific Gastrointestinal Quality of Life Index by mail. To assess the impact of disease-specific factors, 10 questions asking for ability to work, current medication, pouchitis, and extracolonic manifestations of familial adenomatous polyposis were added to the Gastrointestinal Quality of Life Index questionnaire. - RESULTS: - Among 84 patients who answered the questionnaires the median follow-up was 13.4 years (range, 10.3-23.8 y).The results of the Short Form 36 Health Survey were comparable to a German normative population in all dimensions, whereas the overall score for the Gastrointestinal Quality of Life Index was significantly reduced compared with healthy individuals (111.8 vs 120.8, P = .0014). Carcinoma at the time of ileal pouch-anal anastomosis, desmoid tumors, or duodenal adenomas had no significant influence on quality of life. More than 7 bowel movements during the daytime were found to reduce quality of life significantly (103.5 vs 115, P = .0127). More than 2 defecations per night diminished the score further (101 vs 125, P < .0001). Patients younger than 40 years at the time of ileal pouch-anal anastomosis had significantly better results than older patients (120 vs 109.5, P = .0076). - CONCLUSION: - Ileal pouch-anal anastomosis is a safe surgical procedure with a high quality of life comparable to that of a normative population after long-term follow-up of patients with familial adenomatous polyposis.
Gesehen am 14.11.2023